Peningkatan Kreativitas Melalui Pembuatan Karya Cetak dari Bentuk Sekitar Menggunakan Media Flipbook Berbasis Projek Siswa Sekolah Dasar - Galih Miftakhul Khoir; Ika Ari Pratiwi; Sekar Dwi Ardianti (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
This research aims to examine increasing creativity through creating printed works from surrounding shapes using flipbook media based on elementary school student projects. This research applies a quantitative approach. This research is included in Pre-Experimental quantitative research with a One Group Pretest-Posttest Design. This research was carried out at SD 5 Cendono on class II students in the 2024/2025 academic year in Semester I. The data collection technique in this research was a work performance sheet which was carried out by the researcher following the research process by mingling directly with the research object to obtain the required data. The data analysis that the author used in this research used quantitative analysis. The data analysis technique used in this research begins with the normality test, hypothesis, T test and N-Gain test using the SPSS version 25 program. The results of the research show that from the normality test data and hypothesis testing in the Paired Sample T-Test on the pre-test and posttest scores for creativity in making printed works from surrounding shapes using project-based flipbook media, students show an average difference in scores on the creativity pre-test. amounted to 72.0625 and posttest creativity amounted to 84.0625. This has shown that there is a difference and is proven by the results of the paired samples test, namely 0.000 < 0.05 which is declared significant and there is an increase in the average value of the creativity variable for class 2 students with an N-Gain score of 0.4211 and is in the medium criteria. . Thus, it can be concluded that there is an increase in creativity through making printed works from surrounding shapes using flipbook media based on elementary school students' projects.